THE EFFECT OF GIVING TURMERIC EXTRACT AND DRAGON FRUIT SKIN IN DRINKING WATER ON THE PERCENTAGE AND LENGTH OF THE BROILER DIGESTIVE TRACT - Y.F., Yohel,; Dewi, G. A. M. K.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2024)
The rese|arch |aims to determine the effect of giving turmeric extr|act |and dr|agon fruit peel in drinking w|ater on the percent|age |and length of the digestive tr|act of broilers. The rese|arch w|as conducted in Pen|arung|an Vill|age, Mengwi District. This rese|arch l|asted for 28 d|ays, using |a completely r|andomized design consisting of four tre|atments |and four replic|ations. Tre|atment consisted of P0 (0% turmeric extr|act |and dr|agon fruit peel), P1 (4% turmeric extr|act), P2 (4% dr|agon fruit peel extr|act), |and P3 (2% turmeric extr|act + 2% dr|agon fruit peel extr|act). The v|ari|ables observed were the percent|age |and length of the digestive tr|act (proventriculus, ventriculus, duodenum, jejunum, ileum, l|arge intestine |and cecum). The d|at|a obt|ained were |an|alyzed using v|ari|ance, if signific|antly different, continued with the Dunc|an test. The rese|arch results of giving 2% turmeric extr|act + 2% dr|agon fruit peel extr|act (P3) h|ad |an effect on the length of the l|arge intestine, but h|ad no effect on the length (proventriculus, ventriculus length, duodenum length, jejunum length, ileum length, |and cecum length) |and percent|age (proventriculus, percent|age of ventriculus, percent|age of jejunum, percent|age of ileum, percent|age of l|arge intestine, percent|age of cecum). The conclusion of this rese|arch is th|at |administering 2% turmeric extr|act + 2% dr|agon fruit peel extr|act through drinking w|ater c|an incre|ase the length of the l|arge intestine.